Prediction of compounds from breadfruit plants (Artocarpus altilis) as alpha estrogen receptor agonists for novel breast cancer anticancer therapy: an in silico approach - N. Su’aida; R. R. Pratama; A. Fadillah; M. Fauzi (Сибирский онкологический журнал)
The aim of this study was to investigate the potential of compounds from the breadfruit tree (Artocarpus altilis) as anti-breast cancer agents using in silico techniques. Material and Methods. The methods used in this study include molecular docking and ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) predictions to evaluate the interactions with Estrogen Receptor alpha (ERα). Results. Among the 22 compounds tested, Cycloaltisin-7 exhibited the most favorable binding affinity, with a free energy of -10.25 kcal/ mol and an inhibition constant of 30.89 nM. Additionally, Cyclocommunol and Cudraflavone B demonstrated significant binding interactions, with free energies of -9.61 kcal/mol and -9.53 kcal/mol, and inhibition constants of 90.82 nM and 103.50 nM, respectively. For comparison, the standard compound 4-Hydroxytamoxifen showed superior binding characteristics, with a free energy of -12.36 kcal/mol and an inhibition constant of 867.83 pM. ADMET predictions indicate that Cycloaltisin-7, Cyclocommunol, and Cudraflavone B meet essential drug-like criteria, suggesting their potential as viable candidates for further development as breast cancer therapeutics. Conclusion. These findings highlight Cycloaltisin-7 as a particularly promising compound, with Cyclocommunol and Cudraflavone B also showing considerable potential. This research provides valuable insights for the advancement of plant-based treatments for breast cancer.